New development of efficient rock breaking technology with diamond bit - Lina SHEN; Meiling JIA; Jiapin CAI; Haixia WU; Chun LI; Hailong LIU (Jin'gangshi yu moliao moju gongcheng, 2022)
Diamond bit is an important tool for drilling. In recent years, with the application of new composite materials and the continuous progress in precision machining technology, combined with the continuous innovation of drilling equipment, diamond bits have achieved rapid development. This paper briefly introduces some new progress of efficient rock breaking technology with diamond bit, and puts forward the possible development directions in the future.